Forgotten values : the World Bank and environmental partnerships - Kramarz, Teresa; Recorded Books, Inc. (Cambridge, Massachusetts : The MIT Press, 2020)
An examination of the conflict between values and bureaucracy in World Bank biodiversity partnerships that sheds light on this model of global environmental governance. Multi-stakeholder partnerships have become an increasingly common form of global governance. Partnerships, usually between international organizations (IOs) or state agencies and such private actors as NGOs, businesses, and academic institutions, have even been promoted as the gold standard of good governance--participatory, innovative, and well-funded. And yet these partnerships often fail to live up to the values that motivated their establishment. In this book, Teresa Kramarz examines this gap between promise and performance by analyzing partnerships in biodiversity conservation initiatives launched by the World Bank.
OCLC-licensed vendor bibliographic record.
Keywords: elektronické knihy; electronic books; World Bank; Biodiversity conservation -- Economic aspects -- Developing countries; Biodiversity conservation -- Political aspects -- Developing countries; International cooperation